Medieval Bruges, c. 850-1550 - Brown, Andrew 1964-; Dumolyn, Jan 1974- (Cambridge University Press, 2018)
Bruges was undoubtedly one of the most important cities in medieval Europe. Bringing together specialists from both archaeology and history, this 'total' history presents an integrated view of the city's history from its very beginnings, tracing its astonishing expansion through to its subsequent decline in the sixteenth century. The authors' analysis of its commercial growth, industrial production, socio-political changes, and cultural creativity is grounded in an understanding of the city's structure, its landscape and its built environment. More than just a biography of a city, this book places Bruges within a wider network of urban and rural development and its history in a comparative framework, thereby offering new insights into the nature of a metropolis